Exploring Visual, Auditory, and Kinesthetic Learning Modalities for Santri through the Pasti Aksi Pasti Literasi Hanifida Model - Taskiyatul Fikriyah; Rofiatul Hosna; Hanifudin; Asriana Kibtiyah; Khoirotul Idawati (Journal of Contemporary Islamic Education, 2026)
Students engage with learning through diverse visual, auditory, and kinesthetic modalities, yet existing learning models in pesantren have not fully integrated these multimodal learning opportunities. This study aims to explore the implementation of the Pasti Aksi Pasti Literasi Hanifida (PAPLH) model in supporting multimodal learning among santri. A qualitative approach was employed using classroom observations and in-depth interviews with pesantren leaders, teachers, and students. The findings indicate that the PAPLH model fosters a more active and participatory learning environment by integrating literacy exploration, collaborative discussion, knowledge creation, and reflective activities with visual, auditory, and kinesthetic learning modalities. Students demonstrated greater engagement in classroom interactions, improved conceptual understanding, and enhanced digital literacy through activities such as concept mapping, presentations, and educational video production. These findings suggest that the PAPLH model provides an adaptive and inclusive approach to multimodal learning while remaining compatible with the educational values of pesantren. The study contributes to the development of literacy-oriented learning models and offers practical implications for implementing multimodal learning in Islamic educational institutions